Harmoni Dalam Keberagaman: Studi Kasus Interaksi Sosial Umat Hindu dan Islam di Desa Pelangan, Sekotong, Lombok Barat - Hamelia Hamelia (Tabéq: Journal of Local Wisdom, Belief, and Peace, 2025)
Harmony is an ideal condition that is consistently sought after, both within families and in society. This study aims to determine the role of religious leaders in fostering harmony between Hindus and Muslims, and to identify the factors that support and hinder religious harmony in Pelangan Village. This study employs a descriptive qualitative approach, utilising data collection techniques that include observation, interviews, and documentation. The results of the study indicate that interfaith harmony in Pelangan Village is well-established, despite the villagers adhering to different religions. This diversity strengthens solidarity and increases tolerance through positive social interactions. A concrete example of harmony in this village is the community's active participation in mutual assistance activities and mutual support for religious celebrations. This is also due to the active role of the village government and religious leaders as the main drivers in building communication, tolerance, and mutual understanding among residents. Both parties play a crucial role in resolving conflicts, upholding the values of togetherness, and fostering spaces for dialogue among religious communities. Collaboration between formal institutions and community leaders has proven effective in building social harmony amid diversity.